You have to multiple 6 times itself to get the sides
Answer:
![\boxed{2 {x}^{2} - 11x + 11}](https://tex.z-dn.net/?f=%20%5Cboxed%7B2%20%7Bx%7D%5E%7B2%7D%20%20-%2011x%20%2B%2011%7D%20)
Step-by-step explanation:
![= > ( {x}^{2} - 11x + 6) + ( {x}^{2} + 5) \\ \\ = > {x}^{2} - 11x + 6 + {x}^{2} + 5 \\ \\ = > {x}^{2} + {x}^{2} - 11x + 6 + 5 \\ \\ = > 2 {x}^{2} - 11x + 11](https://tex.z-dn.net/?f=%20%3D%20%20%3E%20%28%20%7Bx%7D%5E%7B2%7D%20%20-%2011x%20%2B%206%29%20%2B%20%28%20%7Bx%7D%5E%7B2%7D%20%20%2B%205%29%20%5C%5C%20%20%5C%5C%20%20%3D%20%20%3E%20%20%7Bx%7D%5E%7B2%7D%20%20-%2011x%20%2B%206%20%2B%20%20%7Bx%7D%5E%7B2%7D%20%20%2B%205%20%5C%5C%20%20%5C%5C%20%20%3D%20%20%3E%20%20%7Bx%7D%5E%7B2%7D%20%20%2B%20%20%7Bx%7D%5E%7B2%7D%20%20-%2011x%20%2B%206%20%2B%205%20%5C%5C%20%20%5C%5C%20%20%3D%20%20%3E%202%20%7Bx%7D%5E%7B2%7D%20%20-%2011x%20%2B%2011)
Answer:
(s-t)(-1) = -1
(s+t)(-1) = -7
Step-by-step explanation:
Given the following set of functions
s(x)=2x-2
t(x)=3x
(s-t)(x) = s(t) - t(x)
(s-t)(x) = 2x - 2 - 3x
(s-t)(x) = -x -2
(s-t)(-1) = -(-1) - 2
(s-t)(-1) = 1-2
(s-t)(-1) = -1
(s+t)(x) = s(t) + t(x)
(s+t)(x) = 2x - 2 + 3x
(s+t)(x) = 5x -2
(s+t)(-1) = 5(-1) - 2
(s+t)(-1) = -5-2
(s+t)(-1) = -7
Use the Circumference Formula of a Circle: C=2(pi)(r). The radius is the length from the center to a point on the circle. The circumference is essentially the perimeter of the circle, so the “edge” around the circle is the circumference.